IMPLEMENTASI HAK MILIK ATAS TANAH DALAM TINJAUAN HUKUM ISLAM DAN HUKUM AGRARIA: Studi di Desa Sibowi Kecamatan Tanambulava Kabupaten Sigi - Suardi, Sumarlin; B, M. Taufan; Mubakkirah, Fadhliah; Nafilah, Indri Azkilan (Comparativa: Jurnal Ilmiah Perbandingan Mazhab dan Hukum, 2023)
This article discusses land ownership rights from the perspectives of Islamic law and agrarian law, using a case study in Sibowi Village, Tanambulava Subdistrict, Sigi Regency. The research method employed is a qualitative research approach, with the research location chosen in Sibowi Village, Tanambulava Subdistrict, Sigi Regency. Data sources include primary and secondary data relevant to the researched issues. The research findings indicate that the community of Sibowi Village, Tanambulava Subdistrict, Sigi Regency, had long been managing the land, which was formerly abandoned. In the context of Islamic law, ownership of the land by the community in Sibowi Village is recognized. This recognition is based on the Prophet's hadith regarding reviving barren land, along with the opinions of Syafi'i and Ahmad stating that abandoned lands are not owned by Bayt al-mal but are neutral property (mubah). According to Islamic law, the person who first cultivates (works on) the land is considered its owner. However, from the perspective of agrarian law, formal recognition of ownership rights over the land must comply with the prevailing legal provisions. The acknowledgment of land ownership rights in agrarian law is contingent on formal legality, involving the land registration process, which results in valid proof of ownership, such as a land certificate. Therefore, the land ownership of the Sibowi Village community does not meet the criteria for ownership according to agrarian law.